Peningkatan Nilai Produk Melalui Pendampingan Packaging dan Pemasaran Yang Menarik Pada Industri Rumahan Susu Kedelai Di Desa Sekarputih Kabupaten Pasuruan - Hastari, Sri; Subagio, Dyajeng Puteri Woro; Pudyaningsih, A. Ratna (Universitas Nusantara PGRI Kediri, 2021)
Susu kedelai sekarputih is part of tahu factory in Desa Sekarputih, Kabupaten Pasuruan. Judging from the quality, susu kedelai Sekarputih has an advantage based on delicious and fresh taste compared to another susu kedelai in general. On the other hand, the production process, packaging, and marketing still running traditionally. Susu kedelai was only packaged in an ordinary plastic pouch, less variant, no brand, labels, also information related to product. The product was marketed in limited scope by world of mouth marketing. Unmer Pasuruan’s abdimas team have implemented programs to improve management aspects of marketing, production, finance, and human resources to create attractive susu kedelai product with a higher value that can increase profit and income.